CHRONIC HIVES ASSOCIATED WITH HELICOBACTER PYLORI IN A CHILD - Saeed, Anjum; Assiri, Asaad; Alnimri, Abdulrehman; Majeed, Kashif (Journal of Ayub Medical College Abbottabad, 2013)
Chronic urticaria is fairly a common disorder in children and management is sometime challenging. Helicobacter pylori (H. pylori) should be considered as one of the causes for chronic urticaria when the response to conventional treatment is not appropriate. A nine years old girl with suspicion of wheat allergy (celiac disease) and chronic urticaria was referred for endoscopy. Antral nodularity with H. pylori gastritis was observed and confirmed on biopsy specimen with normal small bowel mucosa. Treatment for H. pylori cured her chronic urticaria. H. pylori should be considered as one of the differential if conventional medication does not help curing chronic urticaria. Key words: Urticaria, H. Pylori, Hives